2021
DOI: 10.4102/sajpsychiatry.v27i0.1637
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of tobacco use amongst South African adults with mental illness in the Eastern Cape

Abstract: Background: Given the physical and mental health consequences of tobacco use amongst individuals with mental illness, it was imperative to assess the burden of tobacco use in this population.Aim: This study examined the patterns and factors associated with tobacco use in individuals attending the outpatient unit.Setting: Cecilia Makiwane Hospital Mental Health Department in Eastern Cape province, South Africa.Methods: Lifetime (ever use) use and current use of any tobacco products were examined in a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…This finding suggests that the smoking rate among SMI individuals in Qatar may be between 2-3 times higher than the rates reported for the general population (21.5%), 18 and is in line with the majority of studies both, worldwide and those within the Middle East region, comparing the smoking rates between SMI samples and those in the general population. 7,16,17,[24][25][26][27][28][29] We also found that smoking was strongly associated with the male gender, which is broadly consistent with the findings in smoking prevalence studies, both in the general population and in people with SMI. 8,16,25,26,[30][31][32] Similarly, as with other studies in the Middle Eastern region, [27][28][29] we found more significant differences in smoking rates in males versus females.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding suggests that the smoking rate among SMI individuals in Qatar may be between 2-3 times higher than the rates reported for the general population (21.5%), 18 and is in line with the majority of studies both, worldwide and those within the Middle East region, comparing the smoking rates between SMI samples and those in the general population. 7,16,17,[24][25][26][27][28][29] We also found that smoking was strongly associated with the male gender, which is broadly consistent with the findings in smoking prevalence studies, both in the general population and in people with SMI. 8,16,25,26,[30][31][32] Similarly, as with other studies in the Middle Eastern region, [27][28][29] we found more significant differences in smoking rates in males versus females.…”
Section: Discussionsupporting
confidence: 87%
“…These differences were broadly consistent with prevalence rates derived from other studies worldwide, which reported the largest smoking rates among those with psychotic disorders. 8,24,[26][27][28][29]37 This diagnostic group in our sample also showed the highest rate of current smokers (51.7%) compared to those diagnosed with mood disorders (32.7% for MDD and 26.2% for bipolar disorder). The most widely accepted hypothesis for the higher prevalence of current smoking among people with psychotic disorders is self-medication; that is, because nicotine stimulates dopamine release in the nucleus accumbens, activating reward pathways, smoking may ameliorate negative symptoms in schizophrenia, and possibly also overcome dopamine blockade by antipsychotic medications.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In one of the few studies conducted in South Africa among PWMI by Tindimwebwa et al in 2020 at the Cecilia Makiwane Hospital in Eastern Cape, 59.4% of 390 outpatient participants reported using tobacco at some point in their lives. 8 The lifetime prevalence of tobacco use differed in various disorders: cannabis-induced disorders (97.3%), schizophrenia (67.9%), bipolar and related disorders (43.5%) and major depressive disorders (36.1%). 8 These rates are even higher among psychiatric inpatients.…”
Section: Epidemiology Of Smoking Among People With Mental Illnessmentioning
confidence: 99%
“… 8 The lifetime prevalence of tobacco use differed in various disorders: cannabis-induced disorders (97.3%), schizophrenia (67.9%), bipolar and related disorders (43.5%) and major depressive disorders (36.1%). 8 These rates are even higher among psychiatric inpatients. In a study conducted among 116 inpatients at Stikland Hospital in the Western Cape, Du Plooy et al 9 found that 91.4% were current smokers.…”
Section: Epidemiology Of Smoking Among People With Mental Illnessmentioning
confidence: 99%